Appearances of family Disintegration for Delinquency females (Journal of the College of Education for Women, 2019)
Family social institution mission in the community, if and repaired Magistrate society and often lead that institution a positive role in the socialization, but a variety of factors ailing infect system family Vtfkdh role effective and influential in society and stands at the forefront of those factors disintegration family, whether caused by the death of one or both parents, divorce or separation, or whether the result of domestic weakness and poor family behavioral practices. And gaining the study of great importance and that the scarcity of studies that address the problem of delinquency female, is no secret that stand on the fact the role of disintegration family in the events of that problem will help and a large degree in the development of recommendations and proposals that limit the severity of the problem, and will therefore strengthen the pillars of the entity's family take turns actor in the proper socialization through work to address the problems of family disintegration and including limits of its devastating effects on children and the result is reflected negatively on the social construction, and research includes six sections have reached an outcome of the most important:1. Shares family disintegration caused the death of one or both parents in juvenile delinquency delinquent females.2. Cases showed that workers faced was where one of the parents are divorced and married the other was the cause of female delinquency.3. Found that the separation of parents and father again marriage was the cause of female delinquency.Among the recommendations proposed by the researcher as follows :1. Work to raise the standard of living of the families to remove poverty, which leads to run an early age girls and help in the school dropout and thus in Jnohan, this task of the Ministry of Labour and Social Affairs.2. Since most delinquent Aaishn in poor areas, it Valdharorh Nstojb work to raise the quality of life in these areas, especially in the area of services, and can contribute to the Ministry of Health and municipalities, Youth and Sports through the provision of health services of water, sewage and building health clinic and sports fields